An Empirical Investigation into Contagion and The Effects of The 2007 Global Financial Crisis On the Cross-Country Linkages Amongst Developed and Emerging Economies, and The Resulting Impact On the Diversification Opportunities for a Global Investor - Kumar, Gagan (2016)
Using data from 12 stock markets the conditional and unconditional correlations around the 2007 global financial crisis are examined across the 2000-2015 period, testing for the effects of contagion spanning across a range of sample periods. A statistical comparison of the Pearson correlation coefficients, Forbes and Rigobon adjusted coefficients, and Engle’s dynamic conditional correlation coefficients, has been conducted in order to determine which method provides the most robust results. It is demonstrated that the DCC model provides the most intuitive and robust estimates for the correlation coefficients as well as assessing the time-varying dynamic nature of these linkages, to display intricate patterns among each market and the corresponding fluctuations in correlations over time. Due to this time-varying nature, it is also found that sample size specification can result in differing interpretations based on the length of time that the sample periods tested around the crisis period are supporting the findings of Dungey and Zhumabekova (2001). Finally, from a novel three-sample testing framework, the nature of linkages can consistently be observed through understanding how the patterns change between markets. Whereby for USA, Canada, Australia, South Africa, Mexico, and Estonia, the correlation patterns suggest a long-term effect of contagion from the UK market upon these markets. Whereas observing the patterns for Australia, India, Turkey, and Argentina these countries display a short-term effect of contagion from the UK in that these markets display signs of recovery, following on from the crisis.